Total Quality Management of the National Amil Zakat Institution in Improving Community Welfare - Rozi, Muhammad Fakrur (Journal of Islamic Economics and Social Science (JIESS), 2023)
The potential possessed by the national amil zakat institution is enormous if Total Quality Management is implemented properly. With the support of the majority of the population who are Muslim, it is appropriate that with such advantages it should be able to increase. Welfare of the Poor and Poor in Indonesia. The research objective is to analyze leadership, continuous improvement, education and training applied to BAZNAS Tulungagung and NU Care-LAZISNU Tulungagung in improving people's welfare. This research is a qualitative research with multi-site research, data collection techniques using in-depth interviews, moderate observation, and documentation, data analysis using the Miles and Hubeman model. Checking the validity of data with Extended Observations, Increased Perseverance, Triangulation and Mamber Check. With the Results of Leadership Research at BAZNAS Tulungagung firm and visionary while NU Care-LAZISNU Tulungagung Honest and Democratic. Continuous improvement at BAZNAS Tulungagung is transparency, improving infrastructure, goat farming programs, and building a culinary center while NU Care-LAZISNU Tulungagung NU Koin, Goat Cultivation, Kulakan Program, and Care for health and education. Education and training at BAZNAS Tulungagung Food Photography program, educational funding assistance, and the SKSS (One Family One Bachelor) program, while NU Care-LAZISNU Tulungagung Madrasah Amil and TOT (Training Of Trainer) program.